Pengolahan Kerupuk Telur Asin Dengan Memanfaatkan Tepung Kemangi Lokal Jenis “Kandangu Mbukku” Pada Konsentrasi Yang Berbeda - Yanti, Seri Uru; Ina, Yessy Tamu; Hambakodu, Marselinus (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study aims to examine the effect of the addition of “Kandangu Mbukku” on the manufacture of salted egg crackers at various levels on organoleptic quality and nutritional value. This study used a completely randomized design with 4 treatments and 5 replications, namely P0: control, P1 Kandangu Mbuku 40%, P2 Kandangu Mbuku 45%, and P3 Kandangu Mbuku 50% P4 Kandangu Mbuku 55%. Data were calculated using Anova test and Duncan's double U2 test. The results showed that the addition of Kandangu Mbuku at different levels had a significant effect P<0.05 on color, taste, texture and level of liking. Nutritional values of moisture content: 5.11%, ash content 1.95%, protein content 1.71%, fat content 30.98%, carbohydrate content 61.24%. The addition of kandangu mbuku leaf extract at the 50% level in making salted egg crackers affects the taste and liking, color, moisture content and pH of the crackers. Meanwhile, the nutritional value of the crackers tends to be stable, because kandangu mbuku leaf extract is not a source of protein, carbohydrates or fat.